A case series: exercise-induced esotropia - Shin, Joseph; Wahl, Birgit; Miller, Neil R.; Singman, Eric L. (American orthoptic journal, 2015)
The authors present three patients with idiopathic exercise-induced esotropia. The history, physical findings, and testing that led to the diagnosis are discussed. To the authors' knowledge, this is the largest series of patients with this rare condition, with this series representing half of reported patients in the literature. It is hoped that a discussion of common features of the condition will guide further exploration of the etiology.